Studies on the Factors Affecting Pathogenicity of Root Rot Caused by Rhizoctonia bataticola in Jatropha curcas - Kumar, S.; Sharma, Sushil (Indian Forester, 2010)
The epidemiological factors viz. inoculum density, inoculum age, inoculum depth and soil moisture affected the root rot development in Jatropha. The inoculum density of 20 g kg-1 soil resulted in 42.22 per cent pre emergence mortality (PEM) and 23.15 per cent post emergence mortality (POEM). The highest PEM (37.78 %) and POEM (21.48 %) were recorded in five days old culture. Inoculum depth at 5 cm induced 42.22 per cent and 30.55 per cent PEM and POEM, respectively. Irrigation schedule at 20 days interval showed maximum PEM (41.66 %) and POEM (34.92 %).